Secondary salinity and waterlogging in the IGNP command area: A threat to agricultural sustainability - Moharana, P C; Singh, R S; Jena, R K; Tailor, B L; Singh, S K (Indian Farming, 2020)
Sustainability of irrigated agriculture in the IGNP command area is potentially threatened by progressively increasing soil salinity. Waterlogging and surface ponding has destroyed the natural environment of the wetland and has caused formation of saline soils. In eventual course, the affected land has become absolutely unfit for agriculture. The progressive increase in soil salinity in the lowland of IGNP area is attributed to unsustainable agricultural practices and inputs, quality of irrigation water, lack of advanced irrigation technologies and efficient drainage systems, and improper land management. Fertilization and irrigation practices should be based upon sound recommendations that consider the pedoclimatic conditions and crop demands. Cost-effective long-term mitigation measures and strategies are urgently encouraged in order to sustain a reasonable soil productivity and quality in irrigated arid region.